PENGEMBANGAN MODEL PROGRAM PEMBELAJARAN INDIVIDU (PPI) BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR INKLUSIF KOTA METRO: PENGEMBANGAN MODEL PROGRAM PEMBELAJARAN INDIVIDU (PPI) BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR INKLUSIF KOTA METRO - ryzal perdana (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
Development of Individual Learning Program (PPI) Model for Children with Special Needs in Inclusive Primary Schools in Metro City. The purpose of this research is to analyze and describe the policy of inclusive education in Metro City through the provision of good services and implementation facilities, to increase the competence of special companion teachers for children with special needs, to produce a model for developing Individual Learning Programs for children with special needs in primary schools that provide inclusive education. Produce graduate masters in education management on time. This study uses a research and development, method which is a research method used to produce a lesson plan (RPP) product. The method used is Research and Development (R & D) with a qualitative approach with a descriptive type. Primary and secondary data sources were obtained from informants selected purposively based on their mastery of inclusive education service management. This research was conducted for four months. This research includes research by the research team lecturers in the form of Individual Learning Program Model Development for Children with Special Needs in Inclusive Elementary Schools in Metro City with postgraduate students of the education management study program FKIP University of Lampung as guidance. The results of this study were addressed to the Metro City Government through the Education and Culture Office as a learning material tool(legal draft)of the individual learning program (PPI) model for children with special needs (ABK) through special companion teachers (GPK) in elementary schools (SD) of Metro City.